Implementation of TOPSIS (Technique for Order of Preference by Similarity to Ideal Solution) in Determining Poverty Ranking of Village Communities as Recommendations for Government Assistance - Hasbul Bahar; Moh. Ainol Yaqin (Unusa Press, 2020)
Since the monetary crisis that hit Indonesia in 1998 it has become a scourge tense for the State of Indonesia. Every year it increases, this thing one of the reasons is the increasing price of food, clothing and food. In response to this, the government has provided several economic assistance, such asFamily Hope Program, KIP (Smart Indonesian Family) and assistance provided by the government. However, there is a lot of assistance the community, especially in the village, admitted to being poor to get this assistance. So that aid was not on target, causing unequal distribution of aid to the community who are indeed poor in accordance with government criteria, as happened, around 1,443 assistance was leveraged or double-checked because it was not right on target. Therefore, we need a ranking concept that is right on target and according to the criteria who are entitled to get assistance from the government by using the TOPSIS method as a recommendation who is entitled to assistance from the government. The fundamental reason for choosing this method is because of the level of complexity so that it has high accuracy when compared to others. And the method will be created using a website, so that it is easily accessible in all places. So, calculating the TOPSIS aims to see the poor in accordance with the criteria set by the government as a recommendation for providing assistance to truly poor people